Analisis Integrasi Artificial Intelligence (AI) Dalam Pembelajaran Maharah Kalam Bahasa Arab - Latifatul Khoiriyah; Luluk Yulia Ma’wa; Ahmad Nur Mizan (Yayasan Al-Afif, 2026)
Conventional Arabic speaking instruction (Maharah Kalam) often faces significant challenges, including limited practice time, lack of interactive environments, and low student confidence. This study aims to analyze the integration of Artificial Intelligence (AI) in developing Maharah Kalam, focusing on its implementation forms, effectiveness, and inherent challenges. Utilizing a qualitative approach with the library research method, data were gathered from reputable journals, books, and scientific publications, then processed through content analysis. The results reveal that AI integration via chatbots, speech recognition, and adaptive platforms such as Duolingo and ChatGPT provides a personalized, interactive, and non-judgmental environment for real-time feedback. These technologies significantly enhance pronunciation accuracy, speaking fluency, and student autonomy. In conclusion, while AI acts as a powerful catalyst for pedagogical innovation, its success relies on a balanced synergy with the teacher’s role in providing cultural context and ethical guidance. This study recommends an adaptive strategy to optimize digital tools for modern Arabic communication proficiency.